Zingiber officinale (ginger): A systematic review and meta-analysis on antimicrobial activities - Nurul Hikmah Harun, Mohamad Firdaus Mohamad (Journal of Applied Pharmaceutical Science, 2023)
The available synthetic drugs to treat infectious diseases have many side effects on the consumer. Zingiber officinale which is known as ginger or “halia” in Malaysia has a good prospect as an alternative for safer treatment and has a low risk of side effects. It is because this herb is used as a traditional medicine in the community to treat several ailments, including infectious diseases. Several studies have shown that crude extracts and bioactive components of Z. officinale possessed diverse pharmacological properties such as anticancer, anti-inflammatory, antimicrobial, antioxidant, and immunomodulatory. The goal of this research is to find out the effects of Z. officinale on antimicrobial activities from the selected previous studies (years 2000–2020). Briefly, this study involves 10 randomized controlled trials (RCTs) that determined the antimicrobial activities of Z. officinale. The results of the systematic analysis showed that Z. officinale exhibits antimicrobial activities for both in vitro and in vivo evaluations. The meta-analysis of appropriate data from four sources presented a substantial distinction between this plant and controls. The results present no significant difference between Z. officinale and positive controls for the antimicrobial analysis related to the overall outcome and inhibition zone [overall outcome standardized mean difference (SMD): −0.6003 (95% CI; −0.7092 to −0.4913), I2 = 100%, inhibition zone SMD: 0.8771 (CI; −8.1288 to 9.8829), I2 = 99%]. In conclusion, the results presented the antimicrobial activities of Z. officinale to be similar to the activity of the positive control. However, one should be aware of some limitations with the detailed reporting on the controls used in the included studies. Future well-designed RCTs with detailed reporting on the controls are required to provide additional data to prove the consequences of Z. officinale on the antimicrobial activities as well as safety data of consuming this plant.
Keywords: Antimicrobial, Zingiber officinale, ginger, meta-analysis, systematic review